Quality of products as an object of management at enterprise - Kharitonova E. A. (Science in figures, 2017)
this article is aimed at studying the problem and the role of product quality management in the production process. External and internal factors of influence on quality management are considered, the primary object of management is revealed, which has a significant impact on quality.
Keywords: производственная деятельность; управление качеством; объект управления; внешние факторы влияния; quality management; внутренние факторы влияния; management object; production operations; external factors of influence; internal factors of influence